Efektivitas Pembelajaran Daring dalam Masa Covid-19 pada Mata Pelajaran Dasar-Dasar Teknik Ketenagalistrikan - Ari Aseh; Usmeldi Usmeldi (Jurnal Pendidikan Teknik Elektro, 2022)
This research is motivated by the difficulties of students in understanding bold learning during the Covid-19 pandemic, and students' difficulties in understanding basic electricity learning which is systematic, logistics full of symbols and surprising formulas during courageous learning. So this study is about the effectiveness of learning to dare to use online media in the subject of Basic Electrical Engineering at SMK 2 Payakumbuh. The purpose of the study was to determine the effectiveness of bold learning on the subject of Electrical Engineering Basics. The researcher carried out this research activity using a quantitative approach with the type of pre-experimental design type one group design (one group pretest posttest design). Multiple-choice written test questions are a data collection technique in the research process carried out. The proportion formula is an analytical technique that researchers use to determine classical learning completeness. Meanwhile, in order to find out how effective the bold learning process was before the learning activities, from the pre-test and post-test using effect size analysis using Cohen's formula. The result of this study is that learning using courage is effective as seen from the students' learning mastery and the result of the effect size test is large or effective, by knowing the various treatments.